2011
DOI: 10.1002/jwmg.219
|View full text |Cite
|
Sign up to set email alerts
|

Suburbs: dangers or drought refugia for freshwater turtle populations?

Abstract: Urbanization is one of the most rapidly expanding forms of habitat alteration worldwide. Wildlife differs in their responses to urbanization depending upon species and site‐specific factors. We used capture‐mark‐recapture to examine the abundance, population demographics, growth, and movements of the eastern long‐necked turtle (Chelodina longicollis) in Australia over 1 year in a suburban environment and an adjacent nature reserve during drought. Contrary to expectations, sex ratios, injury incidence, and freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 62 publications
0
54
1
1
Order By: Relevance
“…2), suggesting turtles were attempting to access habitats and resources within the reserve. Previous research in this system revealed that, before the fence was built, drought conditions forced many turtles to move from the nature reserve into the larger suburban ponds for refuge (Rees, Roe, & Georges 2009;Roe, Rees, & Georges 2011), opposite the predominant direction we observed in our study. During drought, water levels in the nature reserve ponds tend to fluctuate more and experienced greater drying than the suburban ponds (Rees, Roe, & Georges 2009).…”
Section: General Impacts On Reptilescontrasting
confidence: 90%
See 2 more Smart Citations
“…2), suggesting turtles were attempting to access habitats and resources within the reserve. Previous research in this system revealed that, before the fence was built, drought conditions forced many turtles to move from the nature reserve into the larger suburban ponds for refuge (Rees, Roe, & Georges 2009;Roe, Rees, & Georges 2011), opposite the predominant direction we observed in our study. During drought, water levels in the nature reserve ponds tend to fluctuate more and experienced greater drying than the suburban ponds (Rees, Roe, & Georges 2009).…”
Section: General Impacts On Reptilescontrasting
confidence: 90%
“…We used recapture probabilities derived from previous studies using similar trapping protocols in the same study system (Roe, Rees, & Georges 2011). We then calculated population density (number/ha) in the five surveyed ponds and extrapolated density estimates to all ponds within the fenced area to obtain a within-reserve population size estimate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found five studies that examined source-sink dynamics as related to urban spillover. Roe, Rees and Georges (2011) found that urban water sources act as drought refugia for the eastern long-necked turtle (Chelodina longicallis) in Australia, though accessing these desirable urban sites requires individuals from wildland populations to traverse a dangerous urbanized matrix, leading to high mortality and therefore a negative spillover effect on wildland populations. Kauffman, Pollock and Walton (2004) found that coastal populations of peregrine falcons (Falco peregrinus anatum) in southern California preferentially disperse to urban areas, which may act as a pseudo-sink given that the urban areas are used as sources for relocation efforts.…”
Section: Resultsmentioning
confidence: 99%
“…Examination of aerial photos during the drought revealed only two small ponds in the vicinity and it is unlikely that they could support a large number of turtles emigrating away from Elizabeth Lake across a landscape fragmented by roads and low-density housing. Others have demonstrated that turtles will use suburban water bodies during droughts that affect more ephemeral natural wetlands (Roe et al, 2011). However we were unable to sample ponds near Elizabeth Lake.…”
Section: Reduced Body Condition Of Turtles and Poor Water Qualitymentioning
confidence: 96%